The potential influence and intervention measures of gut microbiota on sperm: it is time to focus on testis-gut microbiota axis - Chen, Wenkang; Zou, Hede; Xu, Haoran; Cao, Rui; Zhang, Hekun; Zhang, Yapeng; Zhao, Jiayou (Frontiers in Microbiology, 2024)
As the global male infertility rate continues to rise, there is an urgent imperative to investigate the underlying causes of sustained deterioration in sperm quality. The gut microbiota emerges as a pivotal factor in host health regulation, with mounting evidence highlighting its dual influence on semen. This review underscores the interplay between the Testis-Gut microbiota axis and its consequential effects on sperm. Potential mechanisms driving the dual impact of gut microbiota on sperm encompass immune modulation, inflammatory responses mediated by endotoxins, oxidative stress, antioxidant defenses, gut microbiota-derived metabolites, epigenetic modifications, regulatory sex hormone signaling. Interventions such as probiotics, prebiotics, synbiotics, fecal microbiota transplantation, and Traditional natural herbal extracts are hypothesized to rectify dysbiosis, offering avenues to modulate gut microbiota and enhance Spermatogenesis and motility. Future investigations should delve into elucidating the mechanisms and foundational principles governing the interaction between gut microbiota and sperm within the Testis-Gut microbiota Axis. Understanding and modulating the Testis-Gut microbiota Axis may yield novel therapeutic strategies to enhance male fertility and combat the global decline in sperm quality.